Penggunaan Art therapy Sebagai Bentuk Pencegahan Stress pada Lansia di Panti Jompo - Putri, Nashwa Arika; Zakira, Ichrima; Listiani, Dinda Ayu Nurlita; M, Muslikah; Mahfud, Ashari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Elderly is a phase of life that is marked by various changes in physical, psychological, and social aspects that can trigger stress, anxiety, and even depression. The inability to deal with these changes often causes a decrease in psychological well-being in the elderly, especially for the elderly who live in nursing homes. A non-pharmacological method that is believed to be able to be used to reduce stress levels in the elderly is art therapy. This therapy uses art-based creative activities as a means to channel emotions and support mental health. This study aims to examine the extent to which art therapy is effective in reducing stress levels in the elderly using a literature review approach. A total of 21 relevant scientific articles were reviewed to gain an in-depth understanding of the effect of art therapy on the psychological well-being of the elderly. The results of the study showed that art therapy has a positive impact on reducing stress levels, encouraging self-expression, strengthening coping mechanisms, and providing a sense of calm and meaning for the elderly. Therefore, art therapy can be an effective and applicable intervention to improve the quality of life of the elderly, especially in a nursing home environment.